(untitled) (Research, Society and Development, 2021)
Objective: To outline the socioeconomic and obstetric profile of mothers with preterm children in a municipality in the semi-arid region of Ceará. Methods: This is a descriptive, documentary, retrospective study, with a quantitative approach. The source used for the collection was the database of a municipality in the northern region of the State of Ceará, fed from interviews applied to all mothers who gave birth in local maternity hospitals in 2015. The information was processed using the EPI INFO 6.0 software and Excel 2007 program. Data were analyzed using descriptive statistics. The principles of Resolution 466/2012, approved by the Ethics Committee under protocol number 1.590.501, were respected. Results: The socioeconomic profile of the puerperal women in 2015 was 74.6% in the age group of 20 to 35 years old and 45.7% with an income below the minimum wage 37.8% with complete high school education. As for the obstetric profile, 88.1% had 1 to 3 pregnancies and 51.1% had seven or more prenatal consultations. The prevalent type of delivery was cesarean (69.8%). The complications observed were: urinary tract infection, threat of premature birth and vaginal infection, associated with premature birth. Low-income mothers had higher percentages of urinary tract infection and vaginal infection. Conclusions: The characteristics found in women with premature birth in this study do not differ from the findings in the literature, however, the relationship between urinary infection and prematurity and the influence of socioeconomic conditions on this neonatal outcome was evident.